2007
DOI: 10.1158/0008-5472.can-07-2601
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Loss of Brm Expression in Gastric Cancer Correlates with Histologic Features and Differentiation State

Abstract: The mammalian SWI/SNF chromatin remodeling complex, an essential epigenetic regulator, contains either a single Brm or BRG1 molecule as its catalytic subunit. We observed frequent loss of Brm expression but not of BRG1 in human gastric cancer cell lines. Treatment with histone deacetylase inhibitor rescued Brm expression, indicating epigenetic regulation of this gene, and an RNA interference-based colony formation assay revealed antioncogenic properties of Brm. Brm immunostaining of 89 primary gastric cancers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 47 publications
4
88
1
Order By: Relevance
“…When we exogenously expressed Brm in such deficient cell lines, this resulted in a reduced oncogenic potential, suggesting that Brm has tumor-suppressive properties. This possibility is consistent with our observations that a frequent loss of Brm expression in gastric cancers correlates with a less differentiated state (14). However, the molecular mechanisms underlying the posttranscriptional suppression of Brm remained to be elucidated.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…When we exogenously expressed Brm in such deficient cell lines, this resulted in a reduced oncogenic potential, suggesting that Brm has tumor-suppressive properties. This possibility is consistent with our observations that a frequent loss of Brm expression in gastric cancers correlates with a less differentiated state (14). However, the molecular mechanisms underlying the posttranscriptional suppression of Brm remained to be elucidated.…”
Section: Introductionsupporting
confidence: 92%
“…In terms of the Brm catalytic subunit, we and others have reported that it is frequently deficient in various cancer cell lines such as SW13, AZ521, and C33A (15) and also in primary tumors of the lung (16), stomach (14), and prostate (17). We have, however, further found that a functional Brm gene is present and actively transcribed in all of the Brm-deficient cell lines that we tested in nuclear run-on transcription assays (15,18).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, it is possible that BRG1 could have different, or even opposing, roles depending on the tissue, the factors (oncogenic or anti-oncogenic) with which BRG1 interacts and/or the functional activity of various proteins within the SWI/SNF complex. For instance, while BRM expression is frequently lost in tumors affecting the alimentary tract (in particular gastric carcinomas), BRG1 is usually retained (Yamamichi et al, 2007). In fact, BRG1 may act in an oncogenic manner in some tumors (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…At least haploinsufficiency of BRG1 is recognized [25][26][27]62], while further studies are necessary whether such a role exists for STK11/LKB1 or not. Similar to BRG1, abnormalities of BRM in various cancers have been reported [58][59][60][61][63][64][65][66][67][68][69]. Though the early studies of cell lines and animal models strongly suggested subunits of SWI/SNF proteins as tumor suppressor, the first definitive evidence that members of these complexes function as tumor suppressive was shown by Versteege and colleagues.…”
Section: Roles Of Swi/snf Proteins In Cancermentioning
confidence: 99%